2016
DOI: 10.1038/srep38750
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA miR-1246 induces cell motility and invasion through the regulation of DENND2D in oral squamous cell carcinoma

Abstract: Metastasis is associated with poor prognosis in cancers. Exosomes, which are packed with RNA and proteins and are released in all biological fluids, are emerging as an important mediator of intercellular communication. However, the function of exosomes remains poorly understood in cancer metastasis. Here, we demonstrate that exosomes isolated by size-exclusion chromatography from a highly metastatic human oral cancer cell line, HOC313-LM, induced cell growth through the activation of ERK and AKT as well as pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
127
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(141 citation statements)
references
References 41 publications
7
127
0
Order By: Relevance
“…The expression changes of miRNAs passing through the immunoadsorption column shows the same tendency either using Immusorba or Selesorb. miR‐1246 has been implicated in oral squamous cell carcinoma, where its expression is upregulated in cancer cell‐derived exosomes . Additionally, miR‐1246 expression is reduced by activated B cells via AKT‐p53 signaling pathway in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…The expression changes of miRNAs passing through the immunoadsorption column shows the same tendency either using Immusorba or Selesorb. miR‐1246 has been implicated in oral squamous cell carcinoma, where its expression is upregulated in cancer cell‐derived exosomes . Additionally, miR‐1246 expression is reduced by activated B cells via AKT‐p53 signaling pathway in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, exosomal microRNAs may endow recipient cells with resistance to chemotherapy. Among all miRNAs investigated, miR-1246 has drawn much attention and has been found to function as a proto-oncogene in lung and other cancers [4, 5]. Recently, it was reported that miR-1246 was strongly up-regulated in breast cancer [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bhagirath et al established that miR‐1246 may be a tumor repressor in aggressive prostate cancer that is released via sEV from tumor cells, causing its upregulated expression in body fluids . On the contrary, Sakha et al put forward an opposite view that sEV miR‐1246 stimulates cell motility as well as invasion through by regulating DENND2D in oral squamous cell carcinoma . Coincidentally, Yamada et al found that colorectal cancer cell‐derived microvesicles comprising microRNA‐1246 stimulate angiogenesis by stimulating Smad 1/5/8 signaling prompted by PML downregulation in endothelial cells .…”
Section: Introductionmentioning
confidence: 99%